Detection of the Elusive Nitrogen‐Centered Radicals from Catalytic Hofmann–Löffler Reactions. Issue 40 (24th May 2019) - Bosnidou, Alexandra E.; Duhamel, Thomas; Muñiz, Kilian
Abstract : The catalytic Hofmann–Löffler reaction represents a uniquely effective protocol for the formation of pharmaceutically relevant heterocycles and is based on the reactivity of N‐halogenated amines. Herein, we report stoichiometric experimentation toward the detection of a sulfonamidyl radical as the decisive intermediate in this C‐H amination reaction. It can be observed by EPR after homolytic cleavage of the in situ formed N‐halogen bond under the conditions of the iodine or bromine catalyzed Hofmann–Löffler reaction. Abstract : Detected by EPR: the elusive amidyl radical from heterocycle synthesis by catalytic intramolecular C‐H amination (Hofmann–Löffler reaction).